2019–2020 Florida Citrus Production Guide: Best Management Practices for Soil-Applied Agricultural Chemicals - Davie M. Kapyampakeni; Larry W. Duncan (EDIS)
This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Davie M. Kadyampakeni and Larry W. Duncan, and published by the Horticultural Sciences Department, March 2019.